Organizational Commitment Based on Human Resource Polices Perspective - seyed mohammad erabi; ali bagheri kaljahi (مطالعات مدیریت بهبود و تحول, 2008)
Many researches point out that organizational commitment has remained a topic of interest ever since it was introduced in the early 1950s to the field of organizational behavior, because they believe that properly managed, organizational commitment can lead to beneficial consequences such as organizational effectiveness, improved performance, reduced turnover and reduced absenteeism (Meyer & Allen, 1997; Baruch, 1998; nowadays, 1998; Buck & Watson, 2002; Dixon, 2002). The present study devotes to investigate the effect of human resources management policies as three subsystems: staffing, appraisal and reward, employee relations to the rate of employee organizational commitment and diagnosing the weakness points of these policies. It is shown that there is significant relationship between HRM1 policies and rate of OC2, using the analysis of information which obtains from questionnaire, two dimensional Chi - square test, Gamma and Somers's d correlation coefficient. Also, using one dimensional Chi - square test, we diagnose the problematic HRM policies of the rate of employee organizational commitment.